2012
DOI: 10.1021/bc200650n
|View full text |Cite
|
Sign up to set email alerts
|

α-Acetal, ω-Alkyne Poly(ethylene oxide) as a Versatile Building Block for the Synthesis of Glycoconjugated Graft-Copolymers Suited for Targeted Drug Delivery

Abstract: α-Acetal, ω-alkyne poly(ethylene oxide) was synthesized as building block of glycoconjugated poly(ε-caprolactone)-graft-poly(ethylene oxide) (PCL-g-PEO) copolymers. The alkyne group is indeed instrumental for the PEGylation of a poly(α-azido-ε-caprolactone-co-ε-caprolactone) copolymer by the Huisgen's 1,3 dipolar cycloaddition, i.e., a click reaction. Moreover, deprotection of the acetal end-group of the hydrophilic PEO grafts followed by reductive amination of the accordingly formed aldehyde with an aminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Grafting of the fluoresceinamine was performed according to previously published conditions (Freichels et al, 2012). The procedure is described as follows: the UV-cleaved particles (100 mg, 1 equivalent of aldehyde groups) were suspended in 50 ml of phosphate buffer solution (500mM, pH: 7.4) and fluoresceinamine isomer 1 (2 equivalents) was added.…”
Section: Grafting Of Fluoresceinamine On the Particles Via Reductive Aminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Grafting of the fluoresceinamine was performed according to previously published conditions (Freichels et al, 2012). The procedure is described as follows: the UV-cleaved particles (100 mg, 1 equivalent of aldehyde groups) were suspended in 50 ml of phosphate buffer solution (500mM, pH: 7.4) and fluoresceinamine isomer 1 (2 equivalents) was added.…”
Section: Grafting Of Fluoresceinamine On the Particles Via Reductive Aminationmentioning
confidence: 99%
“…the fluoresceinamine on the particle surface by using reductive amination. Reported conditions for reductive amination reaction by Freichels et al (Freichels et al, 2012) have been followed as described in details in the experimental part. Extensive washing (i.e 3 days) by dialysis had been carefully performed after grafting.…”
Section: Grafting On the Particle Surfacesmentioning
confidence: 99%
“…In vivo , they exhibited better anti-tumor efficacy and reduced toxicity compared to free DOX (Qiu et al, 2013). Other small molecules like biotin (Lin et al, 2013), galactose (Zhong et al, 2013), and mannose (Freichels et al, 2012) have also been reported for surface modification of polymeric micelles.…”
Section: Polymeric Micelles: Background and Relevance As Therapeutic mentioning
confidence: 99%
“…Mannose residues as their 2-aminoethyl glycosides were attached by reductive amination to the surface of copolymer micelles of PEG with poly-ε-caprolactone for targeting dendritic cells and macrophages ( Fig. 4 ) [ 45 ]…”
Section: Reviewmentioning
confidence: 99%